Potential tracers for tracking septic tank effluent discharges in watercourses. (September 2017) - Richards, Samia; Withers, Paul J.A.; Paterson, Eric; McRoberts, Colin W.; Stutter, Marc
Abstract: Septic tank effluent (STE) contributes to catchment nutrient and pollutant loads. To assess the role of STE discharges in impairment of surface water, it is essential to identify the sources of pollution by tracing contaminants in watercourses. We examined tracers that were present in STE to establish their potential for identifying STE contamination in two stream systems (low and high dilution levels) against the background of upstream sources. The studied tracers were microbial, organic matter fluorescence, caffeine, artificial sweeteners and effluent chemical concentrations. The results revealed that tracer concentration ratios Cl/EC, Cl/NH4 -N, Cl/TN, Cl/TSS, Cl/turbidity, Cl/total coliforms, Cl/sucralose, Cl/saccharin and Cl/Zn had potential as tracers in the stream with low dilution level (P < 0.05). Fluorescence spectroscopy could detect STE inputs through the presence of the tryptophan-like peak, but was limited to water courses with low level of dilution and was positively correlated with stream Escherichia coli (E. coli) and soluble reactive phosphorus (SRP). The results also suggested that caffeine and artificial sweeteners can be suitable tracers for effluent discharge in streams with low and high level of dilution. Caffeine and saccharin were positively correlated with faecal coliforms, E. coli, total P and SRP, indicating their potential to trace discharge of a faecal origin and to be a marker for effluent P. Caffeine and SRP had similar attenuation behaviour in the receiving stream waters suggesting caffeine's potential role as a surrogate indicator for the behaviour of P downstream of effluent inputs. Taken together, results suggest that a single tracer alone was not sufficient to evaluate STE contamination of watercourses, but rather a combination of multiple chemical and physical tracing approaches should be employed. A multiple tracing approach would help to identify individual and cumulative STE inputs that pose risks to stream waters in order to prioritise and target effective mitigation measures. Graphical abstract: Highlights: A combined suite of tracers can be a powerful tool of tracking effluent discharge. The ratios of Cl/NH4 -N, Cl/Ba, Cl/TSS and Cl/Zn may be used as effluent tracers. Tryptophan-like peak detection was limited to streams with low level of dilution. Saccharin can be considered as a potential marker for septic tank effluent. Caffeine and artificial sweeteners can be used to track effluent phosphorus. Abstract : A combination of multiple tracers and indicators are the most indicative way of tracking STE discharge, and that factors such as rainfall, stream discharge should be considered before choosing a tracer to evaluate STE contamination.